Integrasi Nilai Budaya dalam Pendidikan Karakter Tanggung Jawab Anak Usia Dini : Sebuah Systematic Literature Review - Siti Khadijah Alam; Husnia Husnia; Fadhilah Sayyidatun Nisa; Hajerah Hajerah; Muhammad Akil Musi (PG PAUD Universitas Islam Makassar | LP2M-UIM | PPJ PAUD (Perhimpunan Pengelola Jurnal PAUD) Indonesia, 2026)
Character education, particularly the value of responsibility, is a crucial foundation for personality formation in early childhood amid digital disruption that risks weakening social interaction and the internalization of local values. This study aims to analyze the effectiveness of integrating local cultural values in shaping responsible character and children's socio-emotional skills, while also formulating a conceptual model for this integration. Using a Systematic Literature Review (SLR) method guided by PRISMA 2020, the search was conducted in the Scopus database (10 May 2026) using the keywords local wisdom, cultural value, character education, responsibility, and early childhood, yielding 13 selected articles (2023–2026). The findings show that the internalization of local wisdom through traditional games (Dakon, Gobag Sodor, Balinese games), socioculturally adaptive bibliotherapy, and local educational philosophies (the teachings of Ki Hadjar Dewantara, the Kauna character) effectively enhances children's responsibility, cooperation, and emotional regulation when pedagogically mediated in accordance with Vygotsky's sociocultural theory and Lickona's character education model. Three main clusters were identified: (1) curricula based on local wisdom, (2) reconstruction of classroom climate through creative media, and (3) sociocultural determinants and the strengthening of educators' cultural competence. The novelty of this research lies in formulating a conceptual model that integrates local culture with sociocultural theory in a manner responsive to the digital era, with the implication that early childhood education (PAUD) curricula need to combine local wisdom with digital literacy so that the formation of responsible character remains contextual and relevant to the times.